Pengelolaan Kecemasan dan Ketidakpastian Dalam Efektivitas Komunikasi Antarbudaya Pada Pertukaran Mahasiswa Merdeka - Christiani, Lintang Citra; Putri, Wahyu Eka; Lase, Formas Juitan (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
Students who participate in exchange programs have to meet people with backgrounds that are much different from their own. Such situations can cause anxiety and uncertainty, which, if not managed, can weaken their motivation to interact with strangers and hinder the educational process. Participants in the Merdeka Student Exchange Program manage anxiety and uncertainty to achieve effective communication. This study aims to explain how anxiety and uncertainty management, based on William Gudykunst's theory, affects the communication effectiveness of inbound students in the Merdeka Student Exchange Program at Untidar and UKI. Using a mixed-method approach with an explanatory sequential design, the research found that the management of anxiety and uncertainty has a positive and significant effect on communication effectiveness, accounting for 73.5% at Untidar and 83.4% at UKI. A key finding is that location and host culture are determining factors; a strong local culture facilitates identification and social categorization, which reduces uncertainty for exchange students. These results reinforce the application of AUM theory in the context of Indonesian student exchange programs and provide practical and social contributions for building effective intercultural communication.